Confidence in the National Immunization Program among parents in Sweden 2016 – A cross-sectional survey. Issue 22 (8th May 2020) - Byström, Emma; Lindstrand, Ann; Bergström, Jakob; Riesbeck, Kristian; Roth, Adam
Highlights: Parents in Sweden are confident and positive towards childhood vaccination. The majority of parents (79%) accept childhood vaccinations without questioning. Most questions are raised with regard to HPV vaccination than the other childhood vaccinations. Among questioning acceptors, questions are most often raised over safety concerns and lack of information. Parents prefer nurses as a source for information on vaccination. Abstract: Background: Vaccination coverage for infant vaccinations in the Swedish National Immunization Program (NIP) has been high for more than a decade, with approximately 97% of 2-year-old children fully immunized. Vaccination coverage against Human Papilloma Virus (HPV) has been around 80% since introduction for girls in 2012. This indicates high parental confidence in the NIP, but as seen in other European countries rapid shifts in confidence may occur. This study examined vaccine confidence and attitudes towards vaccinations among parents in the Swedish population. Methods: A web-based survey was sent to 1046 parents with children aged 0–15 years, in a panel administrated by The Public Health Agency of Sweden. The survey included questions on vaccination awareness, safety and information channels. The response rate was 87%. Data were weighted to adjust for non-responders and for representativeness of the Swedish population. Results: Parents were categorized as acceptors (79%), questioning acceptors (19%) or selective refusers (2%). When excluding responses for HPV vaccination, the proportion of acceptors increased to 91%. The main reasons for questioning or refusing a vaccine were worry over adverse events, negative or lack of information. Along a spectrum of beliefs, acceptors and questioning acceptors were more similar compared to selective refusers. Nurses at child health clinics constituted the most used vaccination information source for acceptors, whereas selective refusers to a greater extent searched information online and in social media. Conclusions: The study demonstrates that parents in Sweden have confidence in and are positive towards vaccinations given within the NIP. One in five parents question vaccines, particularly regarding the HPV vaccine, but still concur to the NIP. Information on vaccines online and at vaccination appointments, including vaccine safety, is important for maintaining confidence in vaccination. Conducting recurring studies is valuable for monitoring vaccine confidence and changes in attitudes towards vaccination.